2021
DOI: 10.1016/j.heliyon.2021.e06028
|View full text |Cite
|
Sign up to set email alerts
|

Increase of complex I and reduction of complex II mitochondrial activity are possible adaptive effects provoked by fluoride exposure

Abstract: Fluoride (F) can induce changes in the expression of several liver proteins, most of them localized in the mitochondria and its effect is dose-and time-dependent. This study analyzed the effect of distinct F concentrations and exposure periods on the mitochondrial activity of complex I-III and II-III in the liver. Thirty-six 21-day-old male Wistar rats were divided into 2 groups (n ¼ 18) according to the duration of the treatment (20 or 60 days). They were subdivided into 3 subgroups (n ¼ 6) according to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…Our results show a general overexpression in complex I while maintaining complex II without alteration. Previous studies have observed increased activity in complex I induced by fluoride along with a reduction in complex II [ 37 ]. These authors indicate that increased activity in complex I could lead to increased ATP and ROS production, and a reduction in complex II could suggest an attempt to reduce energy production to combat increased ROS [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results show a general overexpression in complex I while maintaining complex II without alteration. Previous studies have observed increased activity in complex I induced by fluoride along with a reduction in complex II [ 37 ]. These authors indicate that increased activity in complex I could lead to increased ATP and ROS production, and a reduction in complex II could suggest an attempt to reduce energy production to combat increased ROS [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have observed increased activity in complex I induced by fluoride along with a reduction in complex II [ 37 ]. These authors indicate that increased activity in complex I could lead to increased ATP and ROS production, and a reduction in complex II could suggest an attempt to reduce energy production to combat increased ROS [ 37 ]. Enhanced production of ROS can be highly detrimental and consequently damage macromolecules within mitochondria, including lipids, proteins, and mtDNA [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing some of these key proteins may indicate a desperate attempt to maintain balance in OXPHOS and avoid the activation of apoptotic pathways. Further, we also noticed that the activity of all the complexes decreased upon exposure to the higher dose of NaF [ 59 61 ], increasing the release of superoxide anions and thus increasing ROS levels [ 26 ]. The oxidative stress induced by NaF provokes the dysfunction of the mitochondrial complexes in the skeletal muscle leading to muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recently published systematic review by our group 11 pointed out that the level considered optimum by the WHO is not associated with neurological disorders, whereas higher levels may be associated with lowering the intelligence quotient. To address this issue, we used an experimental design to investigate the association of a low fluoride dose, considered representative of artificial fluoridation of the domestic water supply, and a high fluoride dose, representative of fluoride endemic regions where fluorosis is common, based on molecular, morphological and functional aspects in mice exposed from adolescence to adulthood 12 16 . This window of exposure makes this investigation even more relevant due to the widespread knowledge that at this stage, the central nervous system (CNS) is still developing, presenting similar neurodevelopment events that occur in human children, adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%